1983
DOI: 10.1038/bjc.1983.103
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic killing of human leukaemic lymphoblasts by glucocorticoids and cytosine arabinoside

Abstract: Summary Previous work has shown that the lethal effects of glucocorticoids on the human lymphoblastoid cell line, CEM-C7, are antagonized by the simultaneous presence of 1-,B-D-arabinofuranosylcytosine (Ara-C). A possible cell cycle mechanism prompted further studies using flow microfluorimetry. We now report that (1) Ara-C (10-100nM) blocks cells in S-phase and (2) the block is reversible after the drug is removed. A second treatment protocol, in which glucocorticoid is added to cells recovering from the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1984
1984
1985
1985

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The difference between SAB and SA.SB did not vary significantly from zero when the drugs were combined according to protocol 1, while the only measureable interactions for protocol 2 was a very small antagonistic effect manifested at low HU concentrations. These results are clearly different from the antagonism (protocol 1) and synergism (protocol 2) observed with prednisolone and Ara-C (Gledhill & Norman, 1981;Gledhill et al, 1983). The results presented above show that HU, like Ara-C, inhibited DNA synthesis in CEM-C7 cells, resulting in accumulation of cells in S-phase of the cell cycle (Figure 1).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…The difference between SAB and SA.SB did not vary significantly from zero when the drugs were combined according to protocol 1, while the only measureable interactions for protocol 2 was a very small antagonistic effect manifested at low HU concentrations. These results are clearly different from the antagonism (protocol 1) and synergism (protocol 2) observed with prednisolone and Ara-C (Gledhill & Norman, 1981;Gledhill et al, 1983). The results presented above show that HU, like Ara-C, inhibited DNA synthesis in CEM-C7 cells, resulting in accumulation of cells in S-phase of the cell cycle (Figure 1).…”
mentioning
confidence: 67%
“…Measurement of cellular DNA content by flow microfluorimetry (FMF) confirmed that Ara-C blocked CEM-C7 cells in S-phase, and that the block was reversible (Gledhill et al, 1983). A second treatment protocol (protocol 2) was devised in which the cells were exposed to steroid after prior treatment with Ara-C alone.…”
mentioning
confidence: 99%
See 3 more Smart Citations